The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.2174/0929866525666180614114307
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion Venom Peptides as a Potential Source for Human Drug Candidates

Abstract: The role of peptides in cardiovascular events and in treating osteoporosis signifies their importance. The role of peptides against pathogens, skin infections, pain-relieving effects, anti-malarial and anti-viral effects are discussed in detail. We further, summarized the classification of scorpion peptides among different toxins, their evolutionary process and the pattern of scorpion venom resource analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Actually, venoms from a diverse range of venomous animals have become valuable source for drug development as they are very rich in peptide toxins with high specificity and potency for particular molecular targets (Undheim et al, 2016). Quite a few peptide toxins from BmK venom have been shown to affect ion channel functions, and have anticonvulsant, anti-tumor, and analgesic activities (Uzair et al, 2018). However, no component with anti-inflammatory property has been identified from BmK or scorpion venom (SV) of any scorpion species.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, venoms from a diverse range of venomous animals have become valuable source for drug development as they are very rich in peptide toxins with high specificity and potency for particular molecular targets (Undheim et al, 2016). Quite a few peptide toxins from BmK venom have been shown to affect ion channel functions, and have anticonvulsant, anti-tumor, and analgesic activities (Uzair et al, 2018). However, no component with anti-inflammatory property has been identified from BmK or scorpion venom (SV) of any scorpion species.…”
Section: Introductionmentioning
confidence: 99%
“…It also exhibited the advantage of being able to penetrate deep into tumor tissue [217,218]. Since the discovery of CTx, the list of scorpion crude venoms and isolated toxins with anticancer activity has been growing rapidly, hence a comprehensive review of all reported compounds exceeds the scope of this review, but can be found elsewhere [216][217][218][219]. Here, we present a few cherry-picked recent studies with the most significant findings.…”
Section: Anticancer Effectsmentioning
confidence: 99%
“…Therefore, additional –omic analyses, such as genomics and transcriptomics ( Zhijian et al, 2006 ; Ma et al, 2009 ; Rokyta and Ward, 2017 ; Ward et al, 2018 ), are encouraged to promote the discovery of novel scorpion venom toxins. This research will increase our understanding of Indian red scorpion venom ( Schendel et al, 2019 ), its toxicity mechanism, and identify novel drug prototypes from this venom ( Uzair et al, 2018 ).…”
Section: Conclusion On Future Directions For Research and Augmentation Of Clinical Treatment On Scorpion Stingmentioning
confidence: 99%